Formulation and In Vitro and Skin Permeability Evaluation of Dexamethasone Loaded Niosomal Gel - Hardia, Aarti; Jamindar, Darshan; Mahajan, Amisha; Hardia, Aashish (Asian Journal of Pharmaceutical Research and Development, 2017)
The aim of this work was to prepare a reservoir type transdermal delivery system with the drug core being formed of a Niosomal Gel and to evaluate the permeation. The present study was focused on the screening of dexamethasone loaded Niosomal Suspension and formulation of a Niosomal Gel. Niosomal Suspension of Dexamethasone prepared by Hand Shaking Method using Span 60, Tween 20 and Tween 80 with addition of Charge Inducer. Prepared Niosomal Suspension selected batch show following results Drug Content (98.10±0.885 %), % Entrapment Efficiency (85.27±0.476), Zeta Potential (-23.0 mV) and Invitro Drug Release (74.168± 0.551). Niosomal Gel Prepared by Carbopol 940 and characterized by Drug Content (98.730±0.259), Invitro Cumulative Drug Release (52.962 ±0.226 %). Dexamethasone released from the Plain Gel and permeated 13.499 in 8 hrs; niosomal formulations were able to delay the process up to 29.910 in 8 hrs. The skin permeation increase of dexamethasone was recorded from vesicle Gel in comparison to plain gel. The best fit correlation was found in the Zero order with the R2 value of 0.997. Kinetic model described the release of drug in zero order release model which states the release rate from insoluble matrix is independent of drug concentration. The results indicate that noisome formulation decreased the permeability across gout skin compared with Plain Gel. Niosomal Gel storage under refrigeration showed greater stability. The results suggested that Niosomes could better promote the transdermal delivery of dexamethasone, by their ability to control drug release.